Modern information transformations in information, library and archival affairs - Kvitko, D.; Khomenko, Y. (ХДАК, 2026)
Digitalization of the library services is a process of adding in the library work new technologies that automatize and do work in the library easier and also let create digital documents what is easier to keep and let a distance access to them from web-site or app. For example: KhSAC Library, the Vernadsky Library, The New York Public Library, Libby, the Library App, The Metropolitan Museum of Art, Dovzhenko Centre; etc. They all create digital versions of documents what can be read or watched in website or in app (but the most of library apps need a library card) and you can also see if a library has free paper book, new documents and events.
Keywords: digital libraries; digital information space